The Analysis of Entrepreneurial Leaders on Local Government Performance: Indonesian Evidence - MAHMUDI MAHMUDI (The Indonesian Journal of Accounting Research, 2013)
This study examines the difference of performance between local governments led by entrepreneurs and non-entrepreneurs. The purpose of this study is to examine whether local governments led by entrepreneurs have better performance compared to non-entrepreneurs in terms of local government's revenue (Pendapatan Asli Daerah/PAD) growth, economic growth, level of poverty, and Human Development Index. The sample of this study consists of 102 local governments in West Java, D.I. Yogyakarta, Central Java, and East Java. The data was classified into two groups based on the background of local government leaders; 35 of them were categorized as entrepreneur and 67 werecategorized as non-entrepreneur. The two-sample Mann-Whitney U test is used to analyze the data. This study provides evidence that the performance between local governments led by entrepreneurs and nonentrepreneurs is significantly different. Local governments led by entrepreneurs on average have better performance, measured by PAD growth, economic growth, poverty, and HDI, compared to non-entrepreneurs.